In-between understanding: Witnesses account of the Covid-19 patients’ quarantine journey in the Philippines - Bagual, Eushena Joy; Bandalan, Queenie; Leoveras, Rodelito; Montances, Angel Liela; Nacionales, Joseph; Claridad, Norberto (Yayasan Mitra Persada Nusantara, 2023)
In the year 2020, the world faced a global crisis which brought universal changes to the societal norms; the Covid-19 pandemic. Consequently, the pandemic impair even the daily basis of life as in communicating. This interpretative phenomenological research aims to present the reality of the quarantine journey of the Covid-19 survivors in the Philippines. Through semi-structured interviews, twelve (12) purposively sampled participants drawn out the answers with regard to the questions involving the communication barriers they experienced and the implication of these in their recovery. The thematic analysis revealed nine themes. By which research question 1 emerged with themes (1) uncontrolled factors in isolation centers, (2) poor delivery of message in person, (3) conditional and unsupported medical personnel – to - patient relationship. The second research question revealed the themes (1) mental disturbances constituted by the isolation (2) facilitation boosts amid the quarantine journey, (3) distracting mechanisms by the patients while recovering. The results indicated the communication barriers that the Covid-19 survivors experienced and the implications affecting their recovery.